Psychometric Properties of the Arabic Version of the Behavioral Intention to Interact With Peers With Intellectual Disability Scale - Alnahdi, Ghaleb H.; Schwab, Susanne (Frontiers in Psychology, 2020)
Purpose: According to literature, students' attitudes towards peers with disabilities are crucial for the social inclusion of students with disabilities.Therefore, knowledge about students' behavioral intention to interact with peers with intellectual disability can help improve the social inclusion of students with ID. This study aimed to examine the psychometric properties of the Arabic version of the Behavioral Intention to Interact with Peers with Intellectual Disability Scale.Data were collected from 887 elementary school students (591 female and 296 male) from third to sixth grades in Saudi Arabia.Psychometric properties of the BIS were examined with a confirmatory factor analysis , measurement invariance analysis (across gender), and reliability scales (internal consistency).The results supported the two-dimensional structure of the BIS. The internal consistency of the BIS and each of its subscales was good.Furthermore, no measurement variance was found for male and female students.The Arabic version of the scale showed good psychometric properties and therefore can be recommended to measure students' behavioral intention to interact with peers with intellectual disability.